Employee Capital Plans – public policy analysis - Kolek, Antoni (Lodz University of Technology Press, 2021)
The purpose of this article is to determine on which axiological foundation the system of Employee Capital Plans (EPC) is based and to answer the questions: – how do the authorities want to achieve universal participation in EPC?– what obligations have been imposed on employers, and what are the expected benefits for enterprises?– will investing in EPC funds support the development of the Polish economy? In order to be able to answer the above questions, the first part of the study presents a method of analyzing public policy. Further, the work contains characteristics of behavioral economics mechanisms on which the main ECP institutions were based. Then the Author presents the obligations of employing entities and possible benefits to be achieved by entrepreneurs. In turn, the third part of this article presents the possible benefits for employees.
Keywords: Employee Capital Plans (EPC); public policy analysis